Probiotic potential and safety of enterococci strains - Nascimento, Liane Caroline Sousa; Casarotti, Sabrina Neves; Todorov, Svetoslav Dimitrov; Penna, Ana Lúcia Barretto [UNESP] (Springer Nature, 2019)
The aims of this research were to evaluate the safety and probiotic potential of Enterococcus spp. strains and select novel strains for future development of new functional fermented products. Bile salt hydrolase (BSH) activity, capacity of auto-aggregation and co-aggregation, hydrophobicity, tolerance to different pH values and NaCl content, mucin degradation, and antibiotic susceptibility were evaluated. Considering the preliminary probiotic features and safety, the strains were selected for complementary tests: tolerance to gastrointestinal tract (GIT) conditions, adhesion to Caco-2 cells and β-galactosidase activity, and presence of genes encoding virulence factors, antibiotic resistance, and biogenic amines were also performed for the selected strains. Enterococcus faecium SJRP20 and SJRP65 resisted well to the GIT conditions, presented low adhesion property, produced β-galactosidase although they did not present genes implicated in adhesion, aggregation, and colonization. Enterococcus faecium SJRP65 showed fewer genes related to antibiotic resistance and virulence factors and presented good functional properties, with interesting features for future application in dairy products.
Keywords: Antibiotic resistance; Enterococcus faecium; Lactic acid bacteria; Tolerance to gastrointestinal tract; Virulence factors